UTILIZATION OF CASSAVA PEEL FLOUR FOR PRODUCING SAGO INSTANT NOODLES - Ucok Wandi Siagian; Vonny Setiaries Johan; Usman Pato (Universitas Riau, 2013)
The objective of this research was to find best formulation for making instant noodle from cassava peel flourand sago starch. This study was conducted using Complete Random Design with three repetitions and sixtreatments namely, SK0 (100% sago starch), SK1 (95% sago starch and 5% cassava peel flour), SK2 (90%sago starch and 10% cassava peel flour), SK3 (85% sago starch and 15% cassava peel flour), SK4 (80%sago starch and 20% cassava peel flour), and SK5 (75% sago starch and 25% cassava peel flour). Dataanalyzed using ANOVA (Analysis of Variance) and further analyzed with DNMRT . The results showed thataddition of cassava feel flour significantly affected the moisture content before and after frying, proteincontent, acid value and intactness, but did not significantly influence rehydration time. The best formulationwas SK5 (75% sago starch and 25% cassava peel flour) with moisture content before and after frying 9.12 %and 7.12% respectively, protein content 6.14%, acid number 0.03%, intactness 94.93% and rehydration time4.23 minutes.Key words: instant noodle, cassava peel flour, sago starch